«Empirio» and «ratio» in the visual paradigm of the enlightenment - Ільїна, Г. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article explores the characteristics and understanding of the role of visual perception in the cognitive strategy of the Enlightenment. The relationship between the empirical and rational in realization of the goal of achieving true knowledge is analyzed, the natural-philosophical approach in the analysis of vision is singled out. The role of the metaphor of "light" in the formation of educational ideology and its connection with science is shown.